Level Of Patient Satisfaction With Pharmaceutical Services In The Outpatient Pharmaceutical Room, Mandiraja Community Health Center 1 - Novita Endang Fitriyani; Iva Rinia Dewi; Dian Novita Octavia (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Pharmaceutical services are direct and responsible services to patients with the aim of improving the patient's quality of life. Satisfaction is a feeling of pleasure or disappointment that arises after comparing product performance with expected performance. Satisfaction and service are two things that cannot be separated, with the satisfaction of related parties, they can correct each other how far the improvement in the services that have been provided. Measurement of satisfaction uses five dimensions of service quality, namely tangible evidence (Tangible), responsiveness (responsiveness), assurance (assurance), empathy (Emphaty) and reliability (Reliability). Objective: This study was to describe the level of patient satisfaction with pharmaceutical services in the outpatient pharmacy room at Puskesmas Mandiraja 1. Methods: The type of research was descriptive using a cross sectional approach with the sampling technique of accidental sampling and data collection using questionnaires. Results: Based on the results of calculations on each research indicator the level of patient satisfaction with pharmaceutical services in the outpatient pharmacy room at Mandiraja 1 Health Center is generally categorized as satisfied with the percentage of 75%. The real evidence dimension is 74.15%, the responsiveness dimension is 75.01 %, assurance dimension of 77.44%, the empathy dimension is 75.15% and reliability dimension of 71.07%. Conclusion: Based on the results of the study, the level of patient satisfaction with pharmaceutial services in the outpatient pharmacy room at Puskesmas Mandiraja 1 was in the satisfed category